Instructional Leadership Strategies of School Principals to Enhance Teachers' Competencies in Differentiated Instruction - Supik Atun; Hermanto (International Journal of Social Sciences and Humanities, 2026)
This study aimed to analyze the principal's instructional leadership strategies in improving teacher competence in differentiated learning at SDN 005 Sangatta Utara. The study employed a descriptive qualitative approach. Data were collected through observations, in-depth interviews, and documentation involving the principal, teachers, and the school committee selected purposively. Data trustworthiness was ensured through source triangulation, member checking, and reflection, while data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data collection, data condensation, data display, and conclusion drawing. The findings revealed that the principal implemented four major instructional leadership strategies: teacher capacity development through training and workshops, strengthening an inclusive school culture, improving educational facilities and infrastructure, and enhancing collaboration with internal and external stakeholders. These strategies contributed to improving teachers' pedagogical, professional, personal, and social competencies in implementing differentiated learning. Supporting factors included the principal's commitment, teachers' motivation, a collaborative school culture, and support from the Education Office and the school committee. Meanwhile, the main challenges were limited educational facilities and infrastructure, budget constraints, heavy teacher workloads, uneven understanding of inclusive education, and limited support from Special Education Teachers (SETs).